Delegacia e Defensoria Pública no combate à homofobia em Belém do Pará - NASCIMENTO, Lázaro Castro Silva (Universidade de Santa Cruz do Sul, 2023)
In 2009, in Brazil, have been reported 195 assassinations by homophobia. Of this total, 20 have been reported in north side of the country. This index leads the discussion about the effects of homophobia in Belem of Para. Therefore, we tried to identify what institutions watch over the expected public polices to tackle this kind of violence and what is the understanding by the heads of these institutions about this phenomenon. The Delegacy of Combat to the Discrimination Crimes and the Public Defender’s Office through the Human Being Nucleus were the two researched institutions of Belem. This is an exploratory research in which has been used a qualitative methodology of data collection: bibliographical examination, observation, and semi structured interviews. We detected with the results that: the discussion about homophobia has grown and shown to be increasingly present in the society; the law project which aims to combat homophobia is an important public policy in development. We conclude that the discrimination and the prejudice against sexual orientation pass trough explicit violent acts and hidden acts, for instance, to not witness the seen aggression. The homoerotic sexual orientation still being marginal for escape of the heteronormative standard. In Belem, add to that, there is no space for the full and free experience of living the sexuality without prejudices, which instigates further researches into this topic.